Secure Socket Layer Virtual Private Network (SSL VPN) - Eriek Eriek Orlando (Majalah SIKOMTEK, 2005)
In a fast moving business environment today, a company needs a means of communicationthat has wide coverage and high levels of availability. SSL VPN is a solution using theinternet that already available. Compared to networks or frame relay leased lines, SSL VPNsuse existing infrastructure on the Internet for exchanging data between a corporateheadquarters and branch offices.